Association between peroxisome proliferator-activated receptor-alpha, -delta and -gamma gene (PPARA, PPARD, PPARG) polymorphisms and overweight parameters in physically active men - Maculewicz, Ewelina; Mastalerz, Andrzej; Maciejewska-Skrendo, Agnieszka; Cięszczyk, Paweł; Cywińska, Anna; Borecka, Anna; Garbacz, Aleksandra; Szarska, Ewa; Dziuda, Łukasz; Lorenz, Katarzyna; Łakomy, Roman; Lepionka, Tomasz; et al. (Biology of Sport, 2021)
Peroxisome proliferator-activated receptors (PPARs) have unique functions in energy metabolism regulation but are also involved in regulation of the inflammatory process and obesity. The aim of this study was to analyse potential associations between polymorphisms of PPARA (rs1800206), PPARD (rs1053049; rs2267668) and PPARG (rs1801282) and overweight parameters. One hundred and sixty-six males, unrelated Caucasian military professionals, were recruited in the genetic case-control study conducted in the period 2016–2019. All the participants were aged 21–41 and had similar levels of physical activity. Body mass, height and body composition were measured. The participants were divided into two groups depending on their BMI (body mass index) and FMI (fat mass index). The control group consisted of people with BMI between 20.0 and 25.0 or FMI values ≤ 6, while the overweight group consisted of people with BMI of ≥ 25.0 or FMI values > 6. Genomic DNA was isolated from extracted buccal cells. All samples were genotyped using real-time polymerase chain reaction (real-time PCR). It was found that two polymorphisms rs2267668 and rs1053049 of the PPARD gene were significantly associated with BMI: SNP rs2267668 for the dominant (OR = 2.04, 95%CI 1.01–4.11, p-value = 0.04) model (A/G-G/G vs A/A). The likelihood of being overweight was over 2 times smaller for allele A. A relationship between the polymorphism of PPARG (rs1801282) and BMI was found for the overdominant (OR = 2.03, 95%CI 1.03–4.00, p-value = 0.04) model (C/G vs C/C-G/G). Significant associations were found in different models for PPARD, PPARG and PPARA genes with BMI. In SNP rs2267668 for the codominant genetic model (G/G vs A/A) (p-value = 0.04) and in SNP rs1053049 for the codominant (C/C vs T/T) (p-value = 0.01) and the recessive genetic model (C/C vs T/T–C/T) (p-value = 0.004) all polymorphisms were associated with BMI. In conclusion, it was found that three of the four polymorphisms (rs1053049, rs2267668, rs1801282) selected are associated with the risk of being overweight. Having said that, one has to bear in mind that DNA variants do not fully explain the reasons for being overweight. Therefore more research is needed to make a thorough assessment using the latest genomic methods in sequencing and genotyping, combined with epigenomics, proteomics, transcriptomics, and metabolomics.